Prototype Design of Toxic Gas (CO) Monitoring Equipment in Motorcycle Workshop - Muhammad Hanif Al Hasan; Aris Nasuha (Journal of Robotics, Automation, and Electronics Engineering, 2024)
Workshop is one of the places that contributes a significant amount of carbon monoxide gas, originating from motor vehicle exhaust. A workshop is also a place at high risk of fire. Due to the lack of awareness among visi- tors and workshop workers about the dangers of carbon monoxide gas and the potential for fires in motorcycle workshops, a tool is needed to monitor carbon monoxide levels and detect fire in the workshop. The aim of this final project is to design and develop a device, software, and demonstrate the per- formance of a system for monitoring carbon monoxide levels and detecting fire in a motorcycle workshop. This research uses the Research and Develop- ment (R&D) method. The results of the monitoring system created showed good outcomes. The sensor used was able to read carbon monoxide levels with an error rate of 5.56%, while the Flame sensor was able to detect fire at a maximum distance of up to 70 cm. The monitoring system functioned well, with carbon monoxide levels visualized using ThingSpeak. The DC fan also worked effectively, when carbon monoxide levels in the room reached 25 ppm or higher, the DC fan would turn on and help with air circulation.